Marxist Feminism and Thai Gender Ideals: Patriarchy, Theravada Buddhism, and Generational Shifts in Contemporary Bangkok Thailand as a Case Study - Manowong, Anthika (International Journal of Social Sciences: Current and Future Research Trends, 2024)
In Thai society, the intersection of Theravada Buddhist traditions and patriarchal norms significantly shapes gender roles, particularly regarding domestic labor distribution. While men are typically oriented toward public spheres, women remain largely confined to domestic domains. Our research, drawing from 182 survey responses across four generations, examines how the "Thai Ideal Woman" concept persists through religious- philosophical precepts that reinforce traditional family dynamics. Despite modernization, these cultural norms demonstrate remarkable resilience, with many Thai women internalizing and reproducing traditional gender roles. The data reveals that women consistently perform disproportionate domestic labor compared to their male counterparts. This patriarchal structure, legitimized through religious traditionalism, perpetuates economic disparities by positioning men advantageously while limiting women's socioeconomic mobility. Addressing gender inequality in Thai society requires more than structural reforms; it demands a fundamental reassessment of the religious and social frameworks that historically constrain gender expression.